TRANSFORMATION OF AGGREGATE DEMAND THEORIES IN THE CONDITIONS OF GLOBALIZATION (Development Service Industry Management, 2025)
The aim of the article is to examine the transformation of aggregate demand theories in the context of deepening globalization processes, as well as to identify the key factors influencing their evolution. The author presents an interpretation of the possibilities for adapting fiscal policy to the new challenges of the global economic environment. The theory of aggregate demand is considered as a fundamental concept of modern macroeconomic analysis and as a tool for regulating economic activity. A retrospective analysis of the theory’s development is provided — from the Keynesian model to modern approaches to government regulation that account for the influence of globalization, financial instability, and structural transformations in the global economy.The article employs methods of statistical analysis, theoretical generalization, and graphical grouping and classification.The scientific novelty of the results lies in substantiating and proving that Keynesian theory laid the foundation for the development of modern economic policy, with its central tenet being the necessity of active state involvement in economic regulation, particularly through the stimulation of aggregate demand via fiscal mechanisms. However, in the context of globalization, the effectiveness of the traditional Keynesian approach has significantly diminished, thus creating the need to adapt it to contemporary realities.The practical significance of the research findings is reflected in the analysis of statistical indicators, which demonstrate that classical Keynesian and monetarist approaches, aimed at national-level regulation through fiscal or monetary policy, face constraints under conditions of global integration. The increasing interdependence of national economies, the influence of global factors, and structural transformations necessitate the modernization of existing economic models and the introduction of new approaches to managing aggregate demand.The study of GDP growth dynamics based on purchasing power parity (PPP) for leading world economies made it possible to assess shifts in the global economic weight of these countries. Recommendations are proposed for increasing Ukraine’s share in global PPP-based GDP, particularly through the implementation of the following strategic priorities: diversification of the economy with a focus on high value-added production; support for innovative and technological sectors; attraction of foreign investment and improvement of the business climate; integration into global value chains; and strengthening the country’s macroeconomic stability.
Keywords: aggregate demand; globalization; Keynesian theory; monetarist approaches; fiscal policy; integration